EDUKASI PENGOLAHAN PANGAN FUNGSIONAL BERBASIS POTENSI LOKAL: PEMBUATAN YOGHURT MANGGA PODANG BAGI SISWA SMA - Tiara Ayu Nugraha Putri; Dwi Putri Sunaryanti; Ika Puspitasari Dyah Rahmadhani; Purbowo; Irzaq Galuh Pranata (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The importance of nutrition education and literacy for teens requires an understanding of functional foods made from local ingredients. Conditions in the field show that the habit of choosing nutritious foods has not been well established, and understanding of foods that support digestive health and immunity is still low. This community service activity aims to increase students' knowledge about the concept of functional foods, probiotics, and the use of podang mangoes as a local ingredient in yoghurt production. The methods included interactive lectures, demonstrations, hands-on practice, and participatory observation-based evaluation. The results showed an increase in students' understanding of functional foods and awareness to choose healthier foods. Practice-based learning also made it easier for students to understand how to make economical and easy-to-process podang mango yoghurt. This activity has the potential to encourage entrepreneurial interest in the development of healthy foods and support food security through the optimization of local commodities